2016
DOI: 10.1007/s13592-016-0452-8
|View full text |Cite
|
Sign up to set email alerts
|

The chemical ecology of host-parasite interaction as a target of Varroa destructor control agents

Abstract: -Honey bees and their ectoparasite Varroa destructor communicate through chemical signals among themselves, but they also eavesdrop on each other's chemical cues. We summarize semiochemicals of honey bees and Varroa , and their roles in honey bee-Varroa interactions. We also give an overview of current Varroa control methods, which can be classified into three categories: (1) chemical control methods with acaricides, (2) biotechnical intervention, and (3) bee breeding programs. Widely used synthetic chemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 101 publications
(91 reference statements)
0
45
0
4
Order By: Relevance
“…Furthermore, a colony is genetically diverse hence, the activity of individual hygienic bees is not sufficient to meet the increased demand for task performance (Arathi et al 2006). Studies have shown that olfaction plays a role in hygienic behavior (Masterman et al 2000;Plettner et al 2017) and that the origin of VSH behavior is at least partly related to shifts in antennal gene expression (Mondet et al 2015), therefore, olfactory cues might have played a critical role in the expression of VSH behavior in this study. Worker bees may have detected the presence of different densities of mites in brood cells using these cues other than the previously known fertility signals and the response to these chemical signals seem to be additive as highest removal rates were observed for eight or ten mites compared to five mites singly introduced in closely neighboring brood cells.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, a colony is genetically diverse hence, the activity of individual hygienic bees is not sufficient to meet the increased demand for task performance (Arathi et al 2006). Studies have shown that olfaction plays a role in hygienic behavior (Masterman et al 2000;Plettner et al 2017) and that the origin of VSH behavior is at least partly related to shifts in antennal gene expression (Mondet et al 2015), therefore, olfactory cues might have played a critical role in the expression of VSH behavior in this study. Worker bees may have detected the presence of different densities of mites in brood cells using these cues other than the previously known fertility signals and the response to these chemical signals seem to be additive as highest removal rates were observed for eight or ten mites compared to five mites singly introduced in closely neighboring brood cells.…”
Section: Discussionmentioning
confidence: 72%
“…The two variables were shown to be strongly dependent on the number of mites introduced, an effect that was not seen for the number of cells which were opened only and from which brood and mite were removed. The strong effect of the number of mites on the expression of hygienic behavior is an indicator for the involvement of chemicals in the recognition of mites infesting cells (Nazzi and Le Conte 2016;Plettner et al 2017). VSH bees were more responsive to manipulated brood cells singly introduced with ten mites in a patch of neighboring brood cells as compared to those singly introduced with five mites in a patch of neighboring brood cells probably because the chemical signals that triggers hygienic behavior are less concentrated and harder to detect in brood with low infestation rate (Masterman et al 2001;Martin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as the rear legs are mainly responsible for the mite's locomotion, whereas Varroa forelegs are frequently raised in the air, and can be described as analogous to insect antennae (Eliash et al, 2014;Plettner et al, 2016). This is not surprising, as the rear legs are mainly responsible for the mite's locomotion, whereas Varroa forelegs are frequently raised in the air, and can be described as analogous to insect antennae (Eliash et al, 2014;Plettner et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Honeybee pests are known to cause significant losses, and to transmit viral pathogens for which therapies remain nonexistent and continue to be challenging to eradicate (Plettner et al, 2017). The greater wax moth, Galleria mellonella Linnaeus, is a ubiquitous pest of the honeybee, Apis mellifera.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, they are poisonous to honeybee colonies and non-target species (Ritter and Akratanakul, 2006;Charriere and Imdorf, 1999). Previous researchers have explored various biological agents and bio-products including Bacillus thuringiensis Berliner (Hserotype V) (Plettner al., 2017), but evidence for a successful and sustainable biological control agent of G. mellonela is still lacking. The objective of the present study is to screen different bacterial strains from the cadavers of the greater wax moth reared on laboratory and testing them against the larva of this insect, in order to explore the toxins of these bacteria.…”
Section: Introductionmentioning
confidence: 99%